Maksim Kesantunan Berbahasa Penutur Bahasa Samawa di Desa Labuhan Burung - Gunawan, Hendra; Hermansyah, Wawan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
In communicating, there are people who everyday use polite, ordinary, even rude or sarcastic language, one of which includes speakers of the Sumawa language in Labuhan Burung Village. This study was conducted to determine the maxims of politeness that occur in Samawa language speakers in Labuhan Burung Village. The method used in this research is descriptive qualitative with tapping and recording techniques. Then the data obtained is transcribed, then data reduction and display are carried out. The results of this study contained 6 data on compliance with the maxim of politeness in language, and 4 data on violation of the maxim of politeness in language. There is 1 data each on the maxim of wisdom, the maxim of generosity, the maxim of simplicity, the maxim of consensus, and the maxim of sympathy. As for the violation of the maxim of politeness in language, only four data were found, in the form of a violation of the maxim of consensus, a violation of the maxim of sympathy, a violation of the maxim of appreciation, and a violation of the maxim of generosity. The results of this study indicate that in the Labuhan Burung village community, the observance of the maxim of politeness in language is still more dominant than the violation of the maxim of politeness in language.